Economic Dynamics, Emission Trends and the EKC Hypothesis New Evidence Using NAMEA and Provincial Panel Data for Italy - Massimiliano Mazzanti; Anna Montini; Roberto Zoboli (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper provides new empirical evidence on delinking trends concerning emission-related indicators in Italy. We discuss methodological issues regarding the analysis of delinking and examine the related Environmental Kuznets Curves (EKC) literature to explore and assess the most value added research lines after more than a decade of intensive research in the field. The main contribution of the paper is in providing EKC evidence exploiting environmental-economic merged panel datasets at a decentralized level exploiting long time series and rich cross section heterogeneity at both sectoral and provincial level. This crucially augments the unsatisfactory outcomes deriving from cross country analyses, which are less informative for policy purposes since they provide averages for environmental-economic relationships. Two panel datasets: 1990-2000 emissions at province level; and sectoral disaggregated NAMEA emissions sources for 1990-2001 are analyzed. We find mixed evidence supporting the EKC hypothesis. Some of the pollutants in the NAMEA data, such as CO2, CH4 and CO, produce inverted-U shaped curves with coherent within range turning points. Other emission trends for the period under consideration show monotonic or even N shaped (SOX, NOX, PM10) relationship. Other emissions show relatively less robust results, with mixed evidence arising from different specifications. This partially confirms some of the criticisms directed to EKC empirical investigations. However, our analysis shows that probably there is no single EKC dynamic, but rather many EKC dynamics, differing depending on (i) period of observation; (ii) country/area; (iii) emissions/environmental pressures; (iv) sectors. Sectoral disaggregated analysis highlights that an aggregated outcome should hide some heterogeneity across different sectors. Services tend to present an inverted-N shape in most cases. Manufacturing industry shows a mix of EKC inverted- U and N shapes, depending on the emission considered. The same is true for industry (all industries, not only manufacturing): though a turning point has been experienced, N shapes may lead to increased emissions with respect to very high levels of the income driver. The analysis of provincial data shows that inverted-U shaped curves are present for some of the emissions in the SINAnet- APAT database, such as CH4, NMVOC, CO and PM10, with coherent within range turning points. Other emission trends show a monotonic relationship (CO2 and N2O), or in some cases an inverted-N shaped relationship (SOX and NOX). This kind of analysis at macro sector and/or specific sector level appear to be the most promising and robust field of future research for the assessment of EKC dynamics. National studies grounded in geographical heterogeneity, rather than regional/international analysis, and focused on sectoral trends, are more informative for policy making. The implementation of such investigations needs larger datasets than are currently available. We thus point to the need for increasing and continual effort on constructing integrated environmental/economic statistical accounts.
Keywords: C23; Q38; Q56; 330; Decoupling; NAMEA Emissions; Economic Drivers; Kuznets Curve; Environmental Efficiency